N‐Oligo(3‐hydroxybutyrate)‐functionalized polypyrroles: towards bio‐erodible conducting copolymers. Issue 12 (19th July 2016) - Domagala, Anna; Domagala, Wojciech; Ledwon, Przemyslaw; Musiol, Marta; Janeczek, Henryk; Stolarczyk, Agnieszka; Kurcok, Piotr; Adamus, Grazyna; Lapkowski, Mieczyslaw
Abstract: New copolymer materials have been prepared by chemical grafting of oligomeric 3‐hydroxybutyric acid (OHB) onto polypyrrole (PPy) derivatives. The influence of grafting density and molecular weight of OHB brushes on the physicochemical properties of prepared copolymers was investigated. PPy substrates were prepared by FeCl3 ‐driven oxidative homopolymerization of N ‐(2‐carboxyethyl)pyrrole or its copolymerization with pyrrole. The grafting method employed involved controlled anionic polymerization of β ‐butyrolactone on pyrrole‐tethered potassium carboxylate active sites. Obtained PPy‐ g ‐OHB copolymers of varying grafting density and pendant polyester chain length were characterized and the observed structure–property relationships discussed. The impact of real time exposure to phosphate‐buffered saline environment was investigated and the residue products were characterized. Cross‐correlation of spectroscopic, thermal, electrical and elemental analysis data afforded comprehensive evaluation of the structure of prepared materials and their behaviour in hydrolytic medium. Erosion and degradation pathways have been identified, indicating ways to consciously tailor the physicochemical properties of these new biomimetic materials. © 2016 Society of Chemical Industry Abstract : Polypyrrole copolymers N ‐grafted with 3‐hydroxybutyrate oligomers were synthesized. Adjusting the grafting density and oligomer chain length affords conductive materials with tuneable erodibility in phosphate‐buffered saline environment.